Modeling and Nonlinear Control of a Wind Turbine System Based on a Permanent Magnet Synchronous Generator Connected to the Three-phase Network - Yasser Boussairi; Abdelmajid Abouloifa; Ibtissam Lachkar; Abdellatif Hamdoun; Chaouqi Aouadi (Institute of Advanced Engineering and Science, 2018)
This article presents nonlinear control of wind conversion chain connected to the grid based on a permanent magnet synchronous generator. The control objectives are threefold; i) forcing the generator speed to track a varying reference signal in order to extract the maximum power at different wind speed (MPPT); ii) regulating the rectifier output capacitor voltage; iii) reducing the harmonic and reactive currents injected in the grid. This means that the inverter output current must be sinusoidal and in phase with the AC supply voltage (PFC). To this end, a nonlinear state-feedback control is developed, based on the average nonlinear model of the whole controlled system. This control strategy involves backstepping approach, Lyapunov stability and other tools from theory of linear systems. The proposed state-feedback control strategy is tested by numerical simulation which shows that the developed controller reaches its objectives